Life-Cycle Earnings, Education Premiums, and Internal Rates of Return - Bhuller, Manudeep; Mogstad, Magne; Salvanes, Kjell G. (Journal of Labor Economics, 2017)
Using Norwegian population panel data with nearly career-long earnings histories, we provide a detailed picture of the causal relationship between schooling and earnings over the life cycle. To address selection bias, we apply three commonly used identification strategies. We find that additional schooling gives higher lifetime earnings and a steeper age-earnings profile, in line with predictions from human capital theory. Our preferred estimates imply an internal rate of return of around 11%, suggesting that it was highly profitable to acquire additional schooling. Our analysis reveals that Mincer regressions dramatically understate the returns to schooling because key assumptions are violated.